2012
DOI: 10.5936/csbj.201210011
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Engineering of Biocatalysts for Carboxylic Acids Production

Abstract: Fermentation of renewable feedstocks by microbes to produce sustainable fuels and chemicals has the potential to replace petrochemical-based production. For example, carboxylic acids produced by microbial fermentation can be used to generate primary building blocks of industrial chemicals by either enzymatic or chemical catalysis. In order to achieve the titer, yield and productivity values required for economically viable processes, the carboxylic acid-producing microbes need to be robust and well-performing.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 89 publications
(95 reference statements)
0
13
0
Order By: Relevance
“…coli ’s central Glucose metabolism pathways (tricarboxylic acid (TCA) and Glyoxylate Cycles) and their respective genes, based off ref. [45] and [46]. From these 27 genes, we had data for 26 (we did not find the expression of frdB (b4153) in the E .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…coli ’s central Glucose metabolism pathways (tricarboxylic acid (TCA) and Glyoxylate Cycles) and their respective genes, based off ref. [45] and [46]. From these 27 genes, we had data for 26 (we did not find the expression of frdB (b4153) in the E .…”
Section: Resultsmentioning
confidence: 99%
“…coli metabolic pathways, compiled from ref. [45] and [46]. Most of the genes associated with these metabolic pathways were overexpressed in the spaceflight samples with respect to their matched Earth (1g) controls.…”
Section: Resultsmentioning
confidence: 99%
“…Several reviews and metabolic studies have been published on these mutants [97] but most of these studies indicated that such engineered strains were significantly limited by substrate utilization, especially the C6 and C5 sugars present in lignocellulosic biomass [98]. Mixed microbial consortia such as those present in the rumen, on the other hand, can combine both substrate utilization and targeted product formation through optimizing pathways and fermentation conditions, especially related to high carboxylic acid yields in biorefineries.…”
Section: Disadvantages Of Pure Microbial Cultures In Biorefineriesmentioning
confidence: 99%
“…Escherichia coli and Saccharomyces cerevisiae have been suggested as promising cell factories to produce carboxylic acids, such as lactic, malic, xylonic and succinic acids (see review Alonso, Rendules and Diaz, 2015). Significant titres were obtained with these microbes (Liu and Jarboe, 2012;Toivari et al 2012), although a major limiting factor to overcome during the fermentation process is the product toxicity (Holyoak et al 1999;Piper et al 1998;Piper et al 2001;Nygård et al 2014). Other organisms such as lactic-acid bacteria have been used for industrial purposes, although they have some well-known drawbacks: they have complex nutritional requirements due to their reduced ability to synthesize B-type vitamins and amino acids; they require costly downstream processing approaches and many bacterial species are unable to grow at low pH (Wee et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…However, when the pH is above the pK a of the carboxylic acid, the dissociated or anion form predominates, which implies a mediated transport mechanism to accomplish the uptake/export of the molecule (reviewed by Casal et al 2008). In order to cope with high levels of carboxylic acid production, cell engineering approaches are required to introduce an efficient mechanism to transport the acid out of the cell, avoiding the intracellular accumulation of acid anions, and ultimately increasing the extracellular acid titres (Liu and Jarboe, 2012). …”
Section: Introductionmentioning
confidence: 99%